INTEGRASI MEDIA DAN TEKNOLOGI DALAM MENUMBUHKAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Nurhaliza, Farah; Iren Ramadhanis Sitompul; Deprizon; Zetra Hainul Putra; M Jaya Adi Putra; Neni Hermita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of learning media on the character education of elementary school students at SDN 017 Bukit Payung. The background of the study is based on the increasing use of digital technology by students, which although providing new learning opportunities, also has the potential to disrupt character development if not directed appropriately. The research approach uses a quantitative method with Partial Least Square–Structural Equation Modeling (PLS-SEM) analysis. The research instrument was tested for validity and reliability through outer model analysis, which produced a Cronbach's Alpha value of 0.780 for Learning Media and 0.915 for Character Education. The results showed that learning media had a significant effect on character education, with an R-Square value of 0.870, an effect size of 0.530, and a path coefficient of 0.588 (p < 0.05). These findings indicate that learning media not only functions as a cognitive aid but also has an important contribution in the internalization of students' moral values. This study emphasizes the need for the selection and development of learning media that are not only pedagogically effective but also relevant in building students' character in the digital era.